The Role of Advertising in Shaping Buying Decision of Samsung Mobile Phones: An Application of the DAGMAR Model - Khanal, Meg Nath (Journal of Economics and Management, 2025)
The impact of advertising on customer consumption is a critical area of study in marketing research. This study examines how advertising influences the purchase decisions of Samsung mobile phone consumers, using the Defining Advertising Goals for Measured Advertising Results (DAGMAR) model. The research explores key stages of consumer response to advertising: awareness, comprehension, conviction, and action and evaluates their impact on actual purchase behavior. A well-structured questionnaire was implemented for the collection of data from sample size of 390 from Butwal Sub-Metropolitan City. The findings reveal that awareness, comprehension, and conviction significantly influence purchase decisions, whereas action does not have a statistically significant impact. While advertising plays a crucial role in shaping consumer perceptions and preferences, external factors such as price sensitivity, competitive alternatives, and brand loyalty may also affect the final purchase decision. Descriptive statistics, correlation analysis and multiple regression analysis were applied for the data analysis. The study concludes that Samsung’s advertising strategies effectively enhance consumer knowledge and brand trust but must be complemented by additional marketing efforts to drive conversions.